DAMPAK SOSIAL EKONOMI PEMBANGUNAN JALAN DAN EXIT TOL DI WILAYAH KOTA PEKALONGAN - Nurhayati, Siti; Christianto, Paminto Agung; Zahro, Zahro; Sabana, Choliq (BAPPEDA Kota Pekalongan, 2020)
Pekalongan Municipality Government hopes that the toll exit will be able to help ease access to the Setono Wholesale Market, so that batik traders from outside the municipality who want to shop to Pekalongan faster and easier. However, a growing phenomenon in batik traders in Setono Wholesale Market said that the construction of the toll road caused their sales turnover to decline quite a lot. Meanwhile many people who previously had a livelihood in agriculture had to give up land affected by toll road construction. Even though they get sufficient compensation, to switch professions to find a new job is not easy considering that most farmers do not have other skills. On the other hand, many people have benefited from the existence of toll roads, including the opportunity to find work during the toll road construction season, as well as those who can work in the rest area. Seeing the positive and negative perceptions of the community towards the construction of roads and toll exits, an in-depth and detailed study will be carried out on the socioeconomic impacts on the construction of toll roads and exits that pass through Pekalongan Municipality. Research data will be collected through documentation and questionnaire distribution methods, which will then be processed using descriptive methods. In general, the community stated that the construction of toll roads and exits facilitates transportation access to health servic es and education services, but does not affect the ease of access to government services, and is able to dismiss the issue that the existence of toll roads and exits causes traders' income to fall, but in fact 55.56 % of respondents stated an increase in income and increased the number of kiosks or shops to sell.